Survey sampling - Kish, Leslie (New York : John Willey, 1965)
Introduces students to the design and analysis of sample surveys via a practical, engaging approach. This title begins with brief chapters focused on the important role that sample surveys play in the modern world. It includes exercises that enable students to continue practicing and to stretch their grasp of the content in statistics, survey sampling describes the process of selecting a sample of elements from a target population to conduct a survey.
Includes bibliographical references and index.
aia 03/04/2018
Loans
Keywords: Sampling Statistics; Social surveys; Social Sciences---Research.